Multidisciplinary management of severe odontogenic maxillofacial multi-space infection in a patient with HIV–syphilis coinfection and advanced immunosuppression: a case report - Jieying Li; Yuanyong Feng; Xueqiang Guo; Wei Shang; Kai Zhou (Frontiers in Cellular and Infection Microbiology, 2026)
Background HIV–syphilis coinfection poses a substantial challenge in the management of severe odontogenic infections, with few reports addressing maxillofacial multi-space infections in this setting. Case presentation A 50-year-old man developed severe left maxillofacial multi-space infection one week after molar extraction, presenting with respiratory distress, trismus, elevated C-reactive protein (235.20 mg/L), computed tomography evidence of gas-forming abscesses, reactive HIV antibody, positive syphilis serology, and a CD4+ T-cell count of 133.76 cells/μL. Emergency tracheostomy and incision and drainage were followed by multidisciplinary management comprising sequential antibacterial therapy, intravenous aqueous penicillin G, early antiretroviral therapy, and trimethoprim–sulfamethoxazole prophylaxis. The patient was decannulated on postoperative day 23 and discharged on day 25; the CD4+ T-cell count rose to 321.53 cells/μL within three weeks. At four-month follow-up, the infection had not recurred, the CD4+ T-cell count reached 415.36 cells/μL, and the RPR had reverted to negative. Conclusion In patients with advanced immunosuppression, odontogenic multi-space infection mandates prompt airway control, adequate surgical drainage, sequenced pathogen-specific pharmacotherapy, and multidisciplinary collaboration.